HUBUNGAN PERSEPSI SISWA TENTANG PERAN ORANG TUA DALAM MEMBERI BIMBINGAN BELAJAR DENGAN HASIL BELAJAR SISWA KELAS IV SDN 188 PEKANBARU - Tumiati, Tumiati; Witri, Gustimal; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the low role of parents’ in giving tutoring to 4th grade students at 188 Pekanbaru state elementary school which can be seen from the many students’ who are lazy to learn and the value is still below KKM. The purpose of this study is to determine the relationship of the parents’ role in providing learning guidance with learning outcomes of 4th grade students at 188 Pekanbaru state elementary school. This research was conducted at 188 Pekanbaru state elementary school in August, 2018. This research is quantitative research with a sample of 78 students. The data use in this study is secondary data obtained from questionnaire and data of students’ learning outcomes. Data collection techniques of the parents’ role in providing tutoring are obtained from questionnaires given to students and students’ learning outcomes are obtained from teacher’s value book documentation. Data analysis techniques in this study use software SPSS type 21. The result that there is a significant relationship between the role of parents in providing tutoring with learning outcomes of 4th grade students at 188 Pekanbaru state elementary school with a contribution of 13%.Key Words: The role of parents, tutoring of learning, learning outcomes